Physicochemical and combustion characteristics of hydrochar from banana pseudo-stem by high pressure CO2 hydrothermal treatment - Da LUO; Fenghao JIANG; Li CHEN; Shunxuan HU; Junguo LI; Changning WU; Ke LIU (Meitan xuebao, 2023)
Because of its high moisture content, alkali metal and alkaline earth metal concentration, and low energy density, banana pseudo-stem with huge reserves is difficult to be utilized as fuel. The high pressure CO2 hydrothermal treatment, a non-evaporative wet conversion process, has a greater drying efficiency, as well as a higher removal rate of alkali metals and alkaline earth metals. In addition, the heat value of samples after this treatment are increased. In this study, the SEM, BET, XRD, FTIR, and TG were used to investigate the evolution of physicochemical properties and combustion characteristics of banana pseudo-stem. The results revealed that the hydrochar yield decreases with increasing hydrothermal temperature. In addition, the higher heating value of samples increases from 13.02 to 25.76 MJ/kg with increasing hydrothermal temperature. With increasing hydrothermal temperature, the spatial structure of samples changes from irregular and highly distributed interconnected hierarchically to sheet structure, followed by new three-dimensional configuration porous microstructures. As a result, the specific surface area of the samples firstly increases, then decreases and finally increases with increasing hydrothermal temperature. This phenomenon may improve the combustion performance of the samples. Moreover, the ignition temperature and combustion character index of hydrochar increase at 120−200 ℃ due to the hydrolysis of the hemicellulose and amorphous cellulose. At 200−280 ℃, the ignition temperature and combustion character index of hydrochar decrease due to the transition from cellulose I to cellulose II. Furthermore, the burnout temperature increases with increasing hydrothermal temperature. According to the Flynn-Wall-Ozawa method, the average activation energy of samples are higher than raw samples, except for hydrochar at 280 ℃. Combining the energy recovery rate, ignition temperature, burnout temperature and combustion character index, the optimal temperature for banana pseudo-stem by the high pressure CO2 hydrothermal treatment is found to be 240 ℃.